Survival and Clinical Outcomes of Ovarian Cancer Patients Treated on Phase I Clinical Trials - Corr, Bradley R. (Cancer, 2020)
BACKGROUND: Ovarian cancer patients enrolled in phase I trials are typically platinum resistant, heavily pretreated, with a poor prognosis. We assessed prognostic factors and survival in women with recurrent ovarian cancer treated in phase I clinical trials. METHODS: We performed a retrospective analysis of patients treated from 2008 through 2018 at the University of Colorado Cancer Center. Patient characteristics, treatment and toxicity related survival data were assessed. Descriptive statistics and Cox proportional hazards models were utilized to identify risk factors associated with survival time. RESULTS: 132 patients were treated on phase I clinical trials. Patients had a median age of 59 years (range 33–88) with a median of 5.5 (range 1–13) previous chemotherapy lines. 53/132 (40%) of patients were treated on multiple phase I trials with a median of 1 (range 0–5). Overall response rate was 14.7%. Median overall survival was 11.3 months (95% CI: 9.1–13.4). Two patients died on trial due to progression of disease while no patients died due to treatment-related toxicity. Independent risk factors predicting shorter survival were elevated CA-125 (HR 2.8; 95% CI: 1.6–5.2) and albumin <3.5 g/dL (HR 2.5; 95% CI: 1.65–3.79). BMI >25 predicted longer survival (HR 0.65; 95% CI: 0.44–0.96). CONCLUSIONS: In this single institution series, patients with heavily pretreated ovarian cancer treated in Phase I clinical trials experienced a median overall survival of 11.3 months. Phase I clinical trials represent a reasonable treatment option for heavily pretreated ovarian cancer patients with a preserved performance status when available.